Ansa cervicalis - A new classification approach - Shvedavchenko, Anatoly I.; Oganesyan, Marine V.; Hammer, Christian; Paulsen, Friedrich; Bakhmet, Anastasia A. (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Normally, the inferior root of Ansa cervicalis passes around the internal jugular vein and runs in an anterior direction to meet the superior root ventral to the common carotid artery. However, anatomical variants of the Ansa cervicalis are as yet not well investigated and understood. To close this gap the present study was undertaken. The Ansa cervicalis was examined in 54 human formalin-fixed cadavers and preparations of the head and neck by conventional dissection. In 66% of the specimens the Ansa cervicalis displayed the typical course that was classified as "internal type" (located medial to the internal jugular vein inside the carotid sheath). The remaining 34% pertained to the "external type" of the Ansa cervicalis (lateral to the internal jugular vein). The distance of the Ansa cervicalis relative to the superior margin of the thyroid cartilage was measured in every specimen. The external type Ansa cervicalis was located significantly lower than the internal type relative to the superior margin of thyroid cartilage. Regarding its location relative to the internal jugular vein four variants of combinations of the external and internal types of Ansa cervicalis on the right and left sides were distinguished. Based on their distance from the superior margin of the thyroid cartilage three types of Ansa cervicalis were defined. (C) 2018 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2019-04-18